2014
DOI: 10.1039/c3tc32465f
|View full text |Cite
|
Sign up to set email alerts
|

Spray-coatable ionogels based on silane-ionic liquids for low voltage, flexible, electrolyte-gated organic transistors

Abstract: A new type of silane-based ionogel is demonstrated that can be used in low-voltage electrolyte-gated polymer field-effect transistors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…The anion is associated with the surface and often an additional silica precursor is added to enhance rigidity. 103 In this case the ionic liquid is acting as a liquid phase as it is part of the solid phase. This has led to different interpretations of the term 'ionogel' depending on the research community.…”
Section: Fig 8 Common Ionic Liquid Cation and Anionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anion is associated with the surface and often an additional silica precursor is added to enhance rigidity. 103 In this case the ionic liquid is acting as a liquid phase as it is part of the solid phase. This has led to different interpretations of the term 'ionogel' depending on the research community.…”
Section: Fig 8 Common Ionic Liquid Cation and Anionsmentioning
confidence: 99%
“…In this case there is no free ionic liquid acting as the dispersed phase and the only liquid present comes as a by-product of the sol gel reactions (ethanol and methanol). 103 The ordering of molten salts by the addition of carbon nanotubes has also been employed to form a gel, 113,114 and modified graphene oxide ionic liquid gels have been reported. 145 The sol-gel synthesis of ionic liquid gels have been shown to have an influence on the particle size colour and structure of silica made by the sol-gel process.…”
Section: Macromolecular / Polymer Ionic Liquid Gelsmentioning
confidence: 99%
“…For example, Liu et al printed P3HT above another terrylene semiconductor to make a heterojunction of semiconductor [57]. Thiemann et al spray-coated a layer of ion gel based of silane-ionic liquids on P3HT to obtain advantageous properties such as low modulus, solution processability and high specific capacitance [61]. Magliulo et al modified the surface of P3HT by plasma-enhanced vapor chemical deposition (PE-CVD) of a mixture of ethylene, acrylic acid and argon in a 1:3:1 ratio, which increased the -COOH content at the surface, eventually used to covalently graft phospholipids on the OSC, themselves used to bind biological molecules [64,71,90].…”
Section: Poly(3-hexylthiophene) (P3ht)mentioning
confidence: 99%
“…Like for inkjet-printing, the ink arrives at the substrate as micrometric droplets. For this reason, a challenge for both techniques is to achieve uniform films [52,61].…”
Section: Inkjet Printing and Spray Depositionmentioning
confidence: 99%
“…[136] Ever since Keplinger et al [40] demonstrated the use of an ionic conductor as a deformable and transparent current collector in an actuator, ionic current collectors have been widely used in electronic devices such as touch sensors, [41,40,42] electroluminescence devices, [137][138][139] and axions. [140,141] In the last two years, Suo and co-workers [41] delineated the mechanism of STIC as a current collector Adv.…”
Section: Sticsmentioning
confidence: 99%